2017
DOI: 10.3389/fnins.2017.00366
|View full text |Cite
|
Sign up to set email alerts
|

Common Hepatic Branch of Vagus Nerve-Dependent Expression of Immediate Early Genes in the Mouse Brain by Intraportal L-Arginine: Comparison with Cholecystokinin-8

Abstract: Information from the peripheral organs is thought to be transmitted to the brain by humoral factors and neurons such as afferent vagal or spinal nerves. The common hepatic branch of the vagus (CHBV) is one of the main vagus nerve branches, and consists of heterogeneous neuronal fibers that innervate multiple peripheral organs such as the bile duct, portal vein, paraganglia, and gastroduodenal tract. Although, previous studies suggested that the CHBV has a pivotal role in transmitting information on the status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…CCK is a hormone released from the gastrointestinal tract after meals 50 . It directly influences the afferent fibers of the vagus nerve 51 and is proposed to transmit signals via the NTS 51,52 to various brain regions, including the feeding center.…”
Section: Resultsmentioning
confidence: 99%
“…CCK is a hormone released from the gastrointestinal tract after meals 50 . It directly influences the afferent fibers of the vagus nerve 51 and is proposed to transmit signals via the NTS 51,52 to various brain regions, including the feeding center.…”
Section: Resultsmentioning
confidence: 99%
“…Vagotomy was conducted with slight modifications to previous study (60). Vagotomy was performed under combined triadic anesthesia (Medetomidine Hydrochloride (domitor, ZENOAQ, Japan), Butorphanol Tartrate (vetorphale, Meiji, Japan), midazolam (Sandoz Corporation, Japan)).…”
Section: Vagotomymentioning
confidence: 99%
“…Moreover, an intraoperative neurophysiologic testing observed contractile movement near the duodenum following a stimulation of the hepatic branch [8] . A rodent study demonstrated that the hepatic branch served as vagal afferent nerve for interoception, collecting information from peripheral organs, activating different regions of the brain depending on the nature of stimulus on rats [9] . The celiac branch is known to be associated with the motility of upper gastrointestinal tract.…”
Section: Vagus Functionsmentioning
confidence: 99%